CADANGAN KARBON TANAH SEKITAR DANAU TAMBING DI KAWASAN TAMAN NASIONAL LORE LINDU - Megawati, Kartika; Wardah, Wardah; Arianingsih, Ida (Universitas Tadulako, 2014)
This research aimed to know carbon stock in the soil around Tambing Lake, Lore Lindu National Park area, Sedoa village, Lore Utara district, Poso regency, Central Sulawesi. The collection of soils samples was conducted in June-August, 2013. This study uses survey method two lines with size 20 m x 100 m were place in two sites, in the Lake buffer zone (distance 10 m from the lake shore) and outside of the Lake buffer zone (distance 150 m from the lake shore). Soil sampling was done in three depth layers ; 0-10 cm, 10-20 cm and 20-30 cm. Soil samples was divided into two types, namely undisturbed and disturbed soil. The soil carbon was estimated by analyzing bulk density and soil organic carbon by Walkley-Black method. The results showed that the average carbon stock in the soil around buffer zone of Tambing Lake were 130.95 ton ha-1, 62.02 ton ha-1, 42.71 ton ha-1, in the depth layer 0-10 cm, 10-20 cm and 20-30 cm, respectively. Further, at out buffer zone, the average carbon stock in the soil were 144.51 ton ha-1, 53.55 ton ha-1, 20.71 ton ha-1, respectively. Keywords : Soil carbon, Tambing Lake, Lore Lindu National Park